A Grammar of Christian Faith: Systematic Explorations in Christian Life and Doctrine - Jones, Joe R. (Rowman & Littlefield Publishers, 2002)
A Grammar of Christian Faith is a two-volume set that aims to confront the widespread disarray in the language and practices of Christian faith today. As a 'grammar,' it explains how Christian faith provides special ways of speaking and acting that make sense of human life by giving it meaning, practicality, and hope. It advances the thesis that learning how to speak Christian language in worship and life is crucial to learning how to be a Christian. Rather than supposing that Christian language and theology need continual updating in order to be relevant to the world, Jones urges the church to recover anew how Christian concepts and understanding are intended to form Christian life in all its rich depths. Construing theology as confessional theology in the context of the church, Jones understands the church as that liberative and redemptive community called into being by the Gospel of Jesus Christ to witness in word and deed the triune God for the benefit of the world. The full range of doctrinal themes that are deemed essential to the witness of the church are explored, including clear explanations of why they are essential and how they are to be understood. In pursuit of a truthful and beneficial witness of the church, the work centers on a trinitarian understanding of God, in which God freely and lovingly interacts with the world as Creator, Reconciler, and Redeemer. The work throughout affirms the belief that the gracious triune God is the Ultimate Companion who will redeem all creation.